The Impact of the Use of the Lector Application on the Subject Of Studying the Work of SMPN 3 Pitu Riase. - Rahma; M Hijaz Tahir; Syamsunir; Usman M; Sam Hermansyah (MultiTech Publisher, 2023)
This study uses a quantitative method with the type of experimental research aimed at testing the “Effect of the Use of Lectora Applications on the Learning Results of Students of Class VIII UPT State High School 3 Pitu Riase”. The population of 30 students with Sampling technique using saturated sampling or total samplings. This research variable has two, namely, the free variable Impact of Application Usage of Lectora(X) and its bound variable is the Study Results of Students of Grade VIII of the State High School 3 Pitu Riase (y), this research is carried out at the UPT of State High school 3 Putu Riase. Based on the data analysis, we obtained a value of X=81.93>Y value =70,06 so it can be known that there is an impact of the use of the application of the lecturer on the learning outcome of the students of the eighth grade of the secondary school of the State of 3rd grade. Based upon the results of the research, it is possible to conclude that the impact of using the application for lecturers on the study outcomes of the student of the 8th grade of UPT of the third grade, it shows that the hypothesis of the work stating that there are effects of the Use of the Application of Lectors on the Students of the 3rd degree of the UPT, is acceptable.